Implemetation of Project Based Learning to Increase Creativity And Critical Thinking Abilities of Early Childhood - Natari, Ripa; Rakimahwati, Rakimahwati; Mayar, Farida; Yaswinda, Yaswinda (STKIP Singkawang, 2025)
This study addresses the issue of suboptimal development of children's creativity, often caused by limited opportunities for exploration. Teachers' restrictive approaches hinder children’s creative problem-solving abilities. Using a quasi-experimental method, this research employs purposive sampling, involving two groups: experimental and control, each consisting of 20 children. The study was conducted at two schools, namely UNRI FKIP LAB Kindergarten and Pembina 2 Pekan Baru State Kindergarten. Data collection methods included observation and documentation, with analysis performed using a t-test through SPSS version 26.0 for Windows. The results reveal that project-based learning significantly enhances both creativity and critical thinking skills in young children. This research also highlights active participation and increased understanding among children through contextualized learning through project based learning. This research has limitations as it suggests that early childhood creativity and critical thinking abilities are influenced by more than just project-based learning methods. However, in this research we only looked at two variables, while there are still many other factors that can influence it. It is hoped that future research can examine more deeply the influencing factors, not just two variables